Dynamic attribute-based signcryption without random oracles. (1st January 2012) - Emura, Keita; Miyaji, Atsuko; Rahman, Mohammad Shahriar
In SCN2010, Gagné, Narayan, and Safavi-Naini proposed attribute-based signcryption (ABSC) with threshold structure. As in ciphertext-policy attribute-based encryption (CP-ABE), an encryptor can specify the access structure of decryptors, and as in attribute-based signature (ABS), each decryptor can verify the encryptor's attributes. In contrast to the access structure of decryptors, the access structure of the encryptor needs to be fixed in the setup phase. In this paper, we propose ABSC with dynamic property, where access structures of encryptor can be updated flexibly without re-issuing secret keys of users. We call this primitive dynamic attribute-based signcryption (DABSC). Our DABSC scheme is secure in the standard model under the decision bilinear Diffie-Hellman assumption and the computational Diffie-Hellman assumption.